RESEARCH STAYS AND / OR PRODUCTION FOR OBTAINING MARINE BIOLOGY DEGREE BY THESIS WRITING AT UNIVERSIDAD AUTÓNOMA DE BAJA CALIFORNIA SUR - Gómez del Prado Rosas, María del Carmen (2023)
In higher education, completion efficiency can be measured considering the degree index determined by the completion rate and the number of graduates in a cohort. The Marine Biologist study plan at Universidad Autónoma de Baja California Sur (UABCS) in Mexico, has been modified 11 times. One of the changes included the proposal of the subjects Research Stay and/or Production I and II starting from the 1996-I study plan, continuing up the current 2011-II plan, and adding III and IV, to direct the student toward research work production, which could turn out to be thesis writing. The objective of this work is to determine the possible relationship between Research Stay and/or Production II or III-IV and Marine Biology degree completion by thesis writing with the purpose of assessing completion time between cohorts that studied them with those previous to 1996. The work developed is longitudinal, quantitative, and descriptive. The information obtained was provided by the Office of the Director of Student Services (Dirección de Servicios Escolares), SIIA (Portal de Sistema Integral de Información Administrativa), responsible persons of Research Stay and/or Production II or III-IV programs, and by printed and digital surveys applied to graduates who had completion by thesis writing with 1996-I and 2011-II study plans. The completion efficiency of Research Stay by thesis writing was analyzed using the mean of the time taken by the generations that did not carry out Research Stay and/or Production II or III-IV (Treatment 1) compared to the mean of the time taken by the generations that completed them (Stays II: Treatment 2; Stays III-IV: Treatment 3). A greater percentage of completion rate was observed in those that maintained the thesis topic developed in the Research Stay. These courses contribute to reduce completion time for graduates that choose thesis writing in higher research educations. The average time used by the students in thesis writing in T1 was 3.9 years, 2.4 for those in T2; and 1.2 for those in T3. For the other completion options offered by the University, 50% of Master's credits (Art 73 I) and Automatic Completion by 90-grade point average with no extraordinary exams (Art 73 III), were the ones that have had the most students with completion efficiency.  Keywords: graduates – marine biologist – Mexico – role of a subject – terminal efficiency